O impacto da transformação digital na escola primária: modelo conceitual da sala de aula digital Meu Kamba Cloud em Angola - Pedro, Francisco Xavier (2024)
The revolution brought about by the digital era has profoundly impacted education, affecting teaching, learning and the global educational landscape. Primary schools play a fundamental role in training essential knowledge and skills in the digital context. This study investigates the impact of digital transformation in primary education, using as reference the conceptual model of the digital classroom "Meu Kamba Cloud" in Angola. The research addresses the challenges faced by developing countries, such as Angola and Brazil, by incorporating technology into the educational system, exposing the disparities intensified by the COVID-19 pandemic in access to technology and digital training. The investigation adopts a hypothetical-deductive approach, combining quantitative (Structural Equation Modeling - SEM) and qualitative (Design Science Research - DSR) methods to analyze how digital transformation can reshape the educational environment, making it more dynamic and interactive. The study focuses on the student experience and teaching efficiency, investigating how Digitalization affects the learning of Mathematics, Reading and Science, considering spatial and temporal aspects, with particular attention to fourth and eighth grade classes. The theoretical foundation highlights digital maturity in primary education, correlated with overcoming technological, social and cultural obstacles. The study identified gaps in the impact of digital transformation, especially on digital management and student experience. Future directions were proposed for deepening the empirical model, as well as the development of "Meu Kamba Cloud" in Angola, seeking to offer real-time, high-quality digital teaching-learning. Methodologically, the study employs a robust mixed approach, which integrates statistical analyzes and innovative tools, such as SEM and DSR, to create and evaluate design artifacts in the educational context. The results indicate a significant impact of students' digital skills in Mathematics, Reading and Science, with evidence that introducing the "My Kamba Cloud" model improves performance academic and promotes greater interactivity in the teaching process. The study concludes that the "My Kamba Cloud" effectively addresses the space and time limitations of the model previous, offering a sustainable solution for developing countries such as Angola and Brazil. The positive impact of digital transformation in the primary classroom, especially in Mathematics and Science subjects, suggests that this approach can be replicated in other contexts, contributing to more equitable and quality education. The research reinforces the global relevance of digital transformation in education, highlighting the need for a student-centered approach and technological integration to face the educational challenges of the 21st century.